Studies of radon activity in civil engineering and environmental objects - P. Mikhnev, Ilya; V. Mikhneva, Svetlana; A. Salnikova, Natalia (International Journal of Engineering and Technology, 2018)
In this article, studies of the radiation (radon) characteristics of the soil, soil-forming rocks and civil engineering buildings of the Volgograd Region are presented. The purpose of the study was to identify factors of the radiation background caused by radon in civil engineering objects. The regularities of radon distribution at the objects of the construction complex and the environment are determined depending on the influence of various factors. The studies made it possible to calculate the averaged annual effective equivalent doses to the population of the Volgograd Region caused by radon and the daughter products of the decay of radon. As a result, the patterns of changes in radon activity in the air of the premises have been established, depending on the time of the year, building materials and the purpose of the room. The result of the work performed is the normative material for use in the construction industry in order to limit the radiation exposure of the population in the region. Also, methodological material for training specialists in the field of radiation research in the building complex.Â Â